Effects of rolling motion on flow and heat transfer characteristics in a tube bundle channel. (5th February 2023) - Li, Zongkun; Wang, Meng; Fan, Guangming; Zeng, Xiaobo; Yan, Yiming; Ma, Fubing
Highlights: Two-phase time-averaged heating transfer is lower under rolling motion. Single-phase convection, sub-cooled boiling, and saturated boiling are compared. Effect of rolling motion on the sub-cooled boiling is the most obvious. Instantaneous sub-cooled boiling fluctuation under rolling motion is studied. A model for predicting rolling instantaneous heat transfer coefficient is proposed. Abstract: The usage of nuclear energy in the ocean is growing, and the most significant fundamental motion of ocean conditions is rolling motion. Due to the significant quantity of tube bundle channels in marine nuclear power equipment, it is crucial to investigate the single-phase and boiling heat transfer characteristics in tube bundle channels under rolling motion. The paper compares the single-phase convection, sub-cooled boiling, and saturated boiling heat transfer characteristics under rolling and vertical conditions. The result demonstrates that the two-phase time-averaged heat transfer is lower under rolling motion compared with that under vertical conditions, and the rolling motion has the strongest impact on the time-averaged sub-cooled boiling. Time-averaged heat transfer coefficient decreases with the increase of the rolling amplitude and period. Due to the dearth and the necessity of research on transient sub-cooled boiling under rolling motion, the instantaneous sub-cooled boiling heat transfer fluctuation characteristics are investigated. The fluctuation amplitude of the heat transfer coefficient increases with increasing rolling period and frequency. The change of bubble behavior caused by rolling motion is the main reason for the change of transient heat transfer characteristics compared with that under vertical conditions. At last, a series of correlations based on the Gungor-Winterton correlation is improved and proposed to predict the instantaneous sub-cooled boiling heat transfer coefficient. Thereinto, the average relative error is 7.36% for forecasting the time-averaged heat transfer coefficient, and the average relative error for predicting the fluctuation amplitude of the heat transfer coefficient is 11.58%.